Untowards effects following vaccination in animals - ΣΕΪΜΕΝΗΣ Α.; ΜΕΝΑΣΕ Ι.; ΣΚΥΡΙΑΝΟΣ Γ.; ΣΤΟΦΟΡΟΣ Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
The various forms of untowards effects following vaccination against infectious diseases in animals are discribed. The causes and the possible mechanisms for these manifestations are discussed and measures to avoid them are finally proposed